Opportunities for intermediate temperature renewable ammonia electrosynthesis. Issue 31 (28th July 2020) - Fernandez, Carlos A.; Hortance, Nicholas M.; Liu, Yu-Hsuan; Lim, Jeonghoon; Hatzell, Kelsey B.; Hatzell, Marta C.
Abstract : Intermediate temperature electrosynthesis may allow for large-scale renewable ammonia production. Abstract : Production of ammonia using only renewable energy is achievable through various routes; however, direct electrochemical conversion technologies have achieved significant attention. Despite this attention, the promise for electrochemical ammonia synthesis is unclear, as most electrochemical technology performance is well below that of the Haber–Bosch process (state of the art). Thus, there is a growing interest in defining realistic performance targets which would make renewable ammonia derived from electrochemical systems a reality. However, most efforts thus far have only explored optimizing single technology specific performance metrics such as faradaic efficiency. Optimization of this single performance metric often occurs at the expense of the rate of production which drives implementation and thus can be misleading. Here, we aim to outline the performance targets achievable for renewable ammonia produced through intermediate temperature electrosynthesis. Through exploring the thermodynamic and kinetic challenges, we highlight the optimum expected rate of production and energy efficiency for intermediate temperature electrosynthesis. We also review current experimental reports focused on intermediate temperature ammonia electrosynthesis and detail materials related opportunities in catalyst and solid-electrolyte design. Finally, we discuss some of the challenges related to reporting these desired metrics due to measurement error, and offer solutions to mitigate these challenges.